RELATIONSHIP ANALYSIS OF INDUSTRIAL SECTOR AND TRADE SECTOR TO AUTHENTIC LOCAL REVENUE (PAD) IN THE ERA OF REGIONAL AUTONOMY IN THE CITY SORONG - One, Firawati; Lastari, SE., MM, Siwi; Darini, M.Sc., Dra. Sri (Management, 2010)
This study aims to determine the influence of industry and trade sector acceptance of the PAD in the city of Sorong in the year 2000-2004. The study also sought to give an idea about the role and potential of the economy particularly in the sectors of industry and commerce to the local finance in the era of regional autonomy. The method used in this research is literature study (library research) by using secondary data obtained from the Regional Revenue Office City Sorong. Data analysis was performed with the aid of a computer that is with SPSS for Windows version 11.5. The results of this study suggest a link between the industrial and commercial sectors with PAD is a relationship that is positive and strong relationships in the category. Individually, the relationship between industrial sectors with revenues amounting to 0.847 and the relationship between trade sector with revenues amounting to 0.736. F test (ANOVA) and t test showed that the level of significance of variables and industry trade variable is not significant, because the calculated F value> F table is not met (4.367 t table none was fulfilled which means that individual also does not affect the independent variable. Regression equations generated from regression coefficient calculation is PAD = 417.710 + 7.863 industrial - 7.421 trade. These regression equations or models can not be made to predict the PAD because there are negative signs on the trade variable that should be positive. Also according to the proviso that each independent variable is not significant, the regression model can not be used to predict the independent variable. Keywords: income areas, industry, trade, regional autonomy.